Penguatan Kewenangan Kejaksaan Dalam Melakukan Penyadapan Tindak Pidana Korupsi Menurut Undang-Undang Nomor 16 Tahun 2004 Tentang Kejaksaan - Belmento, Belmento (Lex Librum : Jurnal Ilmu Hukum, 2022)
In Indonesia, corruption involves government and business. Because it's considered a long-term, systematic disease.The study, entitled "The Prosecutor's Authority in Prosecuting Corruption Crimes under the Law No. 16 of 2004 on Prosecutors", suggests that the prosecution has been given additional authority to prevent and combat corruption crimes. The methodology used in this research uses normative research methodology. In addition to the Act No. 16 of 2004 on the Prosecution, the Law No. 19 of 2019 on Electronic Transaction Information regulates the authority of the prosecution to carry out criminal proceedings of corruption. This is done to improve the efficiency and efficiency of prosecution performance because the resulting investigation data can be held accountable. This allows the prosecution to optimize the handling of corruption criminal cases. Criminal acts of corruption include facade acts which are strictly prohibited in Islamic law as they can cause various distortions to the life of the state and society.